2011
DOI: 10.1007/978-1-61779-191-8_8
|View full text |Cite
|
Sign up to set email alerts
|

Studying Permeability in a Commonly Used Epithelial Cell Line: T84 Intestinal Epithelial Cells

Abstract: The integrity, or barrier function, of the intestinal epithelium is of paramount importance in -maintaining good health. This is largely imparted by a single layer of epithelial cells linked by the transmembrane tight junction protein complex near their apical surface. Disruption of epithelial permeability via the tight junctions can contribute to disease progression. The cytokine IFNγ is involved in many inflammatory processes and has been shown to dramatically increase permeability via changes at the tight j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…This cell line is one of several cell lines, such as the CaCo2 and HT-29 cells, used to represent intestinal epithelial cells. T84 cells have also frequently been used as in vitro models for intestinal ion transport and permeability studies and to represent intoxication by ST or endogenous peptides (38)(39)(40). T84 cells express the GC-C receptors in greater numbers than do most other intestinal epithelial cell lines while also maintaining all the components required for signaling and ion secretion that occur secondary to increased cAMP and cGMP (41).…”
Section: Resultsmentioning
confidence: 99%
“…This cell line is one of several cell lines, such as the CaCo2 and HT-29 cells, used to represent intestinal epithelial cells. T84 cells have also frequently been used as in vitro models for intestinal ion transport and permeability studies and to represent intoxication by ST or endogenous peptides (38)(39)(40). T84 cells express the GC-C receptors in greater numbers than do most other intestinal epithelial cell lines while also maintaining all the components required for signaling and ion secretion that occur secondary to increased cAMP and cGMP (41).…”
Section: Resultsmentioning
confidence: 99%
“…Employing monolayers of the T84 human crypt-like epithelial cell line (14,24), we assessed the effect of NSAIDs on epithelial barrier function using noninvasive E. coli as the "permeability probe," since the passage of bacteria across the epithelium may be a critical component of inflammatory bowel disease (1). Corroborating earlier studies (7,42), we show that indomethacin has a significant direct detrimental effect on the barrier function of enteric epithelium, enhancing the transcytosis of the noninvasive, nontoxigenic, nonpathogenic E. coli strain HB101 (used as commensal organisms).…”
Section: Discussionmentioning
confidence: 99%
“…Monolayers of the human T84 crypt-like colonic epithelial cell line have been widely used as an in vitro model system to assess the regulation of epithelial permeability (14,24). Using this model, we found that indomethacin, but not piroxicam [both of which inhibit COX-1 and -2 activity (49)], increased epithelial internalization and translocation of nonpathogenic, noninvasive Escherichia coli.…”
mentioning
confidence: 99%
“…3 Consequently, the paradoxical functions of the intestinal barrier are critical in maintaining gastrointestinal health and homeostasis. 4 Tight junctions provide a paracellular barrier that is selectively permeable to ions and macromolecules. The molecular characteristics and functional properties of tight junctions are subject to modification by a variety of cues, both physiological and pathological, highlighting the highly dynamic nature of these structures.…”
Section: Introductionmentioning
confidence: 99%